Roles of AMP-Activated Protein Kinase (AMPK) in Mammalian Reproduction - Yang, Weina; Wang, Lingjuan; Wang, Fengli; Yuan, Shuiqiao (Frontiers in Cell and Developmental Biology, 2020)
Reproduction is an energy demanding function and only take place in case of sufficient available energy status in mammals. Metabolic diseases such as anorexia nervosa are clinically associated with reduced fertility. AMP-activated protein kinase (AMPK), as a major regulator of cellular energy homeostasis, is activated in limited energy reserves to ensure the orderly progress of various physiological activities. In recent years, mounting evidence shows that AMPK is involved in the regulation of reproductive function through multiple mechanisms. AMPK is likely to be a metabolic sensor integrating central and peripheral signals. In this review, we aim to explore the preclinical studies published in the last decade that investigate the role of AMP-activated protein kinase in the reproductive field, and its role as a target for drug therapy of reproductive system-related diseases. We also emphasized the emerging roles of AMPK in transcriptional regulation of reproduction processes and metabolisms, which are tightly related to the energy state and fertility of an organism.